Application of CRISPR-Cas9 genome editing technology in various fields: A review - Ansori, Arif NM.; Antonius, Yulanda; Susilo, Raden JK.; Hayaza, Suhaila; Kharisma, Viol D.; Parikesit, Arli A.; Zainul, Rahadian; Jakhmola, Vikash; Saklani, Taru; Rebezov, Maksim; Ullah, Md. Emdad; Maksimiuk, Nikolai; Derkho, Marina; Burkov, Pavel (Narra J, 2023)
CRISPR-Cas9 has emerged as a revolutionary tool that enables precise and efficient modifications of the genetic material. This review provides a comprehensive overview of CRISPR-Cas9 technology and its applications in genome editing. We begin by describing the fundamental principles of CRISPR-Cas9 technology, explaining how the system utilizes a single guide RNA (sgRNA) to direct the Cas9 nuclease to specific DNA sequences in the genome, resulting in targeted double-stranded breaks. In this review, we provide in-depth explorations of CRISPR-Cas9 technology and its applications in agriculture, medicine, environmental sciences, fisheries, nanotechnology, bioinformatics, and biotechnology. We also highlight its potential, ongoing research, and the ethical considerations and controversies surrounding its use. This review might contribute to the understanding of CRISPR-Cas9 technology and its implications in various fields, paving the way for future developments and responsible applications of this transformative technology.